Nutritional status of 1-5 years children in the urban slum area of Jagdalpur city, Bastar region, Chhattisgarh - Khan, Q. H.; Arora, Garima; Nalli, Susheel Kumar (International Journal Of Community Medicine And Public Health, 2018)
Background: Nutritional status is the best indicator of the child health. Malnutrition has both short and long term adverse ramifications. As per NFHS III 47% children are stunted in the state of Chhattisgarh. However still many communities in the tribal dominated and naxal affected state may remain affected, hence the study was planned to identify the nutritional status of children and find out its determinant. Methods: Present cross-sectional study was conducted among 12-59 months children in the urban slum of Jagdalpur city, Bastar region of Chhattisgarh. Predesigned and pretested questionnaire was administered to the caregiver of the child, information on socio-demographic characteristics was obtained and anthropometric measurements were taken. Statistical Analysis: all frequencies were derived for completeness of data. WHO Anthro Software version 3.1.0 was used to classify the malnutrition status. Chi-square test was applied to find association between dependent variables. Results: Out of 225 children 53.3% were boys and 46.7% were girls. The overall prevalence of underweight stunting and wasting was 28.4%, 41.3%, and 19.1% respectively. Conclusions: Prevalence of underweight has reduced in the district over a period of years. However high level of stunting, a sign of chronic hunger points towards the pivotal role of socio-demographic and behavioral practices prevalent in the district. Interaction with health system in the form of ANC, institutional delivery and safeguarding effective 100% immunization coverage has shown preventive effect.